Marketing Politics: Political Participation of Beginner Voters In Electing The President of 2019 - Runik Machfiroh; Ama Suyanto (Universitas of Muhammadiyah Makassar, 2020)
. Political marketing in the 2019 presidential election is one of the main factors of Indonesian democracy. The brand personality of the 2019 presidential candidates became an important point in the victory of the 2019 presidential election. The millennial generation is part of the target of novice voters. Previous research has carried out mapping and analysis of political marketing in the 2014 presidential election, 2014 legislative elections, and the 2015 regional elections where in each election there were differences in emphasis in political marketing. The purpose of this study is to analyze the uniqueness of political marketing in the 2019 presidential election compared to previous political marketing. This research approach uses quantitative research with descriptive methods with statistical descriptive data analysis. The population of this research is novice voters in West Java. The sampling technique used was random sampling with a total sample of 100 respondents. The results of this study indicate that 100% of beginner voters use digital media to find out presidential candidates and 80% to add to their basic political knowledge. However, the presidential election decision based on the media only reached 57.6%.Keywords: Political Marketing, Political Participation, Political Education, Beginner Voters, Presidential ElectionsMarketing politik dalam pemilihan Presiden Tahun 2019 menjadi salah faktor utama demokrasi Indonesia. Brand personality dari kandidat calon presiden 2019 menjadi poin penting dalam kemenangan pemilihan presiden 2019. Generasi milenial adalah bagian dari target pemilih pemula. Penelitian sebelumnya telah dilakukan pemetaan dan analisis marketing politik pada pemilihan presiden 2014, pemilihan legislatif 2014, dan pemilihan kepala daerah 2015 di mana dari setiap pemilihan terjadi perbedaan penekanan dalam marketing politik. Tujuan penelitian ini adalah menganalisis keunikan marketing politik pemilihan presiden tahun 2019 dibanding marketing politik sebelumnya. Pendekatan penelitian ini menggunakan penelitian kuantitatif dengan metode deskriptif dengan analisis data deskriptif statistik. Populasi penelitian ini adalah pemilih pemula di Jawa Barat. Teknik sampling yang digunakan adalah random sampling dengan total sampel 100 responden. Hasil penelitian ini menunjukkan bahwa 100% pemilih pemula menggunakan media digital untuk mengetahui calon presiden dan 80% untuk menambah pengetahuan dasar politik. Namun, keputusan pemilihan presiden berdasarkan media hanya mencapai 57.6%.Kata Kunci: Marketing Politik, Partisipasi Politik, Pendidikan Politik, Pemilih Pemula, Pemilihan Presiden